Vladimir Ilyich Lebedev: The geologist and the patriot of Tuva (to the 75th anniversary) - Soyan, Mergen K. (The New Research of Tuva, 2010)
Vladimir Ilyich Lebedev: The geologist and the patriot of Tuva (to the 75th anniversary)